STRATEGI KOMUNIKASI DA’I DALAM MENANAMKAN NILAI-NILAI AGAMA BAGI ANAK-ANAK JALANAN DI KECAMATAN MEDAN SUNGGAL - Rholand Muary (Jurnal Ilmiah Sosiologi Agama (JISA), 2019)
Tujuan Penelitian adalah untuk mengetahui metode penelitian komunikasi Da’i dalam Menanamkan Nilai-Nilai Agama kepada Anak-anak Jalanan, hambatan dari komunikasi Da’i dalam Menanamkan Nilai-Nilai Agama kepada Anak-anak Jalanan di Pinang Baris Kecamatan Medan Sunggal. Penelitian ini menggunakan metode penelitian kualitatif dengan pendekatan fenomenologi. Teknik pengumpulan data dalam penelitian ini adalah observasi dan wawancara. Hasil yang diperoleh pada penelitian ini adalah Strategi komunikasi Da’i dalam menanamkan nilai-nilai agama kepada anak-anak jalanan di Pinang Baris Kecamatan Medan Sunggal terdapat beberapa bentuk. Pertama Da’i memberikan pengarahan sepenuhnya dan berupaya memberikan motivasi kepada mereka agar mau bersekolah. Kedua Da’i menunjukkan ketauladanan dalam kehidupan sehari-hari. Ketiga mengajarkan anak-anak jalanan melaksanakan shalat, membaca Al-Qur’an dengan memberikan pengarahan agar dapat diamalkan mereka dalam kehidupannya. Hambatan-hambatan yang didapatkan dalam menanamkan nilai-nilai agama kepada anak-anak jalanan yaitu sulit diatur (bandel), kurangnya pengawasan (kontrol) ketika mereka berada di jalanan dan faktor lingkungan yang tidak kondusif.The aim of the study was to find out the communication method of Da'i in Infusing Religious Values to Street Children, obstacles from Da'i's communication in Instilling Religious Values with Street Children in Pinang Baris, Medan Sunggal District. This study uses qualitative research methods with a phenomenological approach. Data collection techniques in this study were observation and interviews. The results obtained in this study are Da'i's communication strategy in instilling religious values with street children in Pinang Baris, Medan Sunggal Subdistrict, there are several forms. First Da'i gave full direction and tried to motivate them to go to school. Both Da'i show obedience in everyday life. The third teaches street children to pray, read the Qur'an by giving instructions so that they can be practiced in their lives. Obstacles obtained in instilling religious values to street children are unruly (stubborn), lack of supervision (control) when they are on the streets and non-conducive environmental factorsThe aim of the study was to find out the communication method of Da'i in Infusing Religious Values to Street Children, obstacles from Da'i's communication in Instilling Religious Values with Street Children in Pinang Baris, Medan Sunggal District. This study uses qualitative research methods with a phenomenological approach. Data collection techniques in this study were observation and interviews. The results obtained in this study are Da'i's communication strategy in instilling religious values with street children in Pinang Baris, Medan Sunggal Subdistrict, there are several forms. First Da'i gave full direction and tried to motivate them to go to school. Both Da'i show obedience in everyday life. The third teaches street children to pray, read the Qur'an by giving instructions so that they can be practiced in their lives. Obstacles obtained in instilling religious values to street children are unruly (stubborn), lack of supervision (control) when they are on the streets and non-conducive environmental factors. Keywords: Da'I Communication, Religious Values